Case Report: Vincristine-induced acute pancreatitis in pediatric Wilms tumor: first reported case challenging previous risk classifications and proposing vigilant monitoring protocols - Liu, Ting; Cao, Zhongqiang; Lai, Fangyuan; Xu, Huanli; Chen, Zebin; Yuan, Xiuli; Liu, Xiaoya (Frontiers in Pediatrics, 2026)
Vincristine, a cornerstone vinca alkaloid in pediatric oncology, has historically been regarded as a low-risk agent for drug-induced acute pancreatitis (DIAP). We report the first documented pediatric case of vincristine monotherapy-associated acute pancreatitis, challenging existing toxicity paradigms. A 3.25-year-old boy with stage IV Wilms tumor developed acute-onset fever and localized periumbilical pain 48 h after vincristine infusion (0.9 mg), administered within standard dosing. Laboratory testing confirmed marked pancreatic hyperenzymemia (serum α-amylase 2,022 U/L, 12.5 × ULN; lipase 568 U/L, 7.1 × ULN), and contrast-enhanced ultrasonography revealed pancreatic edema. A Naranjo score of 7 indicated probable causality, further supported by complete symptom resolution after substitution with vindesine and no recurrence during six months of follow-up. Genetic testing showed no CEP72 (rs924607) susceptibility variant, suggesting a hypersensitivity rather than pharmacogenomic mechanism. This case highlights the need to re-evaluate vincristine's DIAP risk profile in children and supports implementing routine post-infusion monitoring of pancreatic enzymes in high-risk patients. Vindesine may serve as a safe and effective alternative agent. These findings underscore the importance of updating pediatric chemotherapy safety guidelines for vinca alkaloid-containing regimens.